Inequality and Immigration - Christian Dustmann; Yannis Kastis; Ian Preston (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates the relationship between immigration and inequality in the UK over the past forty years. This is a period when the share of foreign-born in the UK population increased from 5.3% in 1975 to 13.4% in 2015. We evaluate the impact immigration had on wage inequality in the UK through two channels: the first is the effect on the earnings distribution of the natives and the second is the effect on the composition of the wage-earning population. We find both effects to be very small. We decompose wage inequality into inequality within the immigrant and native group and inequality between the two groups. We find inequality among immigrants to be consistently higher than inequality among natives. We also examine the impact of immigration on the fiscal budget, and the potentially unequal impact of the ensuing tax implications on natives. In the UK, where immigrants are net fiscal contributors, this is not a factor that aggravates economic inequality. Even though the impact of immigration is found to be small, the way it is perceived across different population groups in the UK varies; a fact mostly attributed to racial and cultural concerns rather than perceived economic competition.
Keywords: 330